Endoscopically assisted extralevator abdominoperineal excision. (December 2015) - Buchs, N. C.; Kraus, R.; Mortensen, N. J.; Cunningham, C.; George, B.; Jones, O.; Guy, R.; Ashraf, S.; Lindsey, I.; Hompes, R.
Abstract: Aim: Extralevator abdominoperineal excision (ELAPE) has been advocated to optimize clearance of lower third rectal cancers with an involved or threatened circumferential resection margin. ELAPE could reduce positive margins and specimen perforation compared with standard abdominoperineal excision. However, there can be difficulties with ELAPE, particularly in identifying the anterior plane in male patients. Usually, the dissection is performed in the prone position, which can be hazardous, particularly in obese patients in whom wound problems are commonly encountered. We describe an endoscopically assisted approach for ELAPE in the lithotomy position. Method: Three male patients with a rectal tumour located at the anorectal junction underwent an endoscopically assisted ELAPE in the lithotomy position after preoperative radiotherapy. Results: All the procedures were performed successfully with operation times of 180, 390 and 420 mins. There were no instances of intra‐operative perforation or other complications. One patient developed postoperative intestinal obstruction which resolved on conservative management. There were no wound complications. Histopathological examination demonstrated clear margins and intact mesorectal planes in each patient. Conclusion: We report a good outcome in three patients after endoscopically assisted ELAPE. This approach allows the patient to be operated on in the lithotomy position giving excellent views of the anterior dissection.